2012
DOI: 10.4028/www.scientific.net/amr.512-515.375
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Study on Vacuum Pyrolysis Reaction of Chinese Fir Sawdust Biomass

Abstract: This thesis does thermal gravimetric analysis(TGA)studies on Chinese fir sawdust biomass by integrated thermal analyzer under vacuum conditions. Through the analysis on lostmass curve at different heating rate of 10, 15, 20 and 30°C/min, we found the process of Chinese fir sawdust vacuum pyrolysis can be mainly divided into three stages: evaporation of free water and combined water desorption, rapid lostmass of pyrolysis and slow decomposition of residues. The lostmass major temperature range is between 250 ~ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Sawdust is one of the biomass from wood waste. Various studies (Yang et al 2012) showed that sawdust was the potential for renewable energy. The energy value per mass of sawdust is 17 MJ/kg when viewed from a very competitive price compared to Liquefied petroleum gas (LPG) with a value of 30 MJ/kg (Kan et al, 2013).…”
Section: Literature Review 21 Syngas Production From Sawdustmentioning
confidence: 99%
See 1 more Smart Citation
“…Sawdust is one of the biomass from wood waste. Various studies (Yang et al 2012) showed that sawdust was the potential for renewable energy. The energy value per mass of sawdust is 17 MJ/kg when viewed from a very competitive price compared to Liquefied petroleum gas (LPG) with a value of 30 MJ/kg (Kan et al, 2013).…”
Section: Literature Review 21 Syngas Production From Sawdustmentioning
confidence: 99%
“…The Fischer-Tropsch technique is one of the commercially accessible methods of manufacturing clean synthetic fuel from syngas and others. The process to produce syngas using require energy from the outside (Yang et al, 2012). The lack of this process requires additional fuel to produce syngas.…”
Section: Literature Review 21 Syngas Production From Sawdustmentioning
confidence: 99%